ANALISIS YURIDIS RANGKAP JABATAN DIREKTUR PT SHOPEE INTERNATIONAL INDONESIA DAN PT NUSANTARA EKSPRES KILAT - NIM. A1011211278, ELVI TURSINA FIRANTI (Jurnal Fatwa Hukum, 2025)
Abstract Interlocking directorates by the Director of PT Shopee International Indonesia and PT Nusantara Ekspres Kilat violates Article 26 of Law No. 5 of 1999 due to indications of unfair business competition during the interlocking directorate period. According to investigation by the Indonesian Competition Commision (KPPU), Shopee has discriminately prioritized its internal delivery service, Shopee Express. It was demonstrated that this interlocking directorates act is affecting the policies of businesses, which consequently had an impact on competition within the respective market. Article 26 of Law No. 5 of 1999 does not impose an absolute prohibition on holding interlocking directorates act itself, but it mandates an analysis to determine if such roles lead to monopolistic practices and/or unfair business competition. The type of research conducted is normative juridical with descriptive analysis, using the rule of reason approach and case approach. The data was collected using technique involves literature research, then analyzed by interpreting Law No. 5 of 1999 in relation to the behavior of interlocking directorates by the director in PT Shopee International Indonesia and PT Nusantara Ekspres Kilat. There are indication that the interlocking directorates by the Director of PT Shopee International Indonesia and PT Nusantara Ekspres Kilat violates Article 26 of Law No. 5 of 1999. This interlocking directorates is to result in significant legal implications for the policies implemented on the Shopee platform. Shopee is alleged to have engaged in discriminatory practices in selecting delivery services on its platform, which constitutes a violation of Article 19 letter (d) of Law No. 5 of 1999. KPPU conducted its first hearing concerning Shopee"™s alleged breach of Law No. 5 of 1999 in May 2024. Keywords: interlocking directorates, director, Shopee platform Abstrak Jabatan rangkap yang dilakukan oleh Direktur PT Shopee International Indonesia dan PT Nusantara Ekspres Kilat melanggar Pasal 26 UU No. 5 Tahun 1999 karena dalam masa jabatannya terdapat indikasi persaingan usaha tidak sehat. Sebagaimana hasil investigasi KPPU bahwa Shopee secara diskriminatif memprioritaskan layanan pengiriman internalnya, Shopee Express. Jabatan rangkap ini terbukti memengaruhi kebijakan pelaku usaha, yang pada akhirnya kebijakan tersebut berdampak pada persaingan di pasar yang bersangkutan. Ketentuan Pasal 26 UU No. 5 Tahun 1999 tidak secara mutlak melarang jabatan rangkap, melainkan harus menganalisis apabila jabatan rangkap tersebut mengakibatkan terjadinya praktik monopoli dan/atau persaingan usaha tidak sehat. Jenis penelitian yang digunakan adalah yuridis normatif bersifat deskriptif analisis dengan menggunakan pendekatan rule of reason dan case approach, teknik pengumpulan data berupa literature research yang kemudian data akan dianalisis dengan menginterpretasikan UU No. 5 Tahun 1999 dalam perilaku rangkap jabatan direktur di PT Shopee International Indonesia dan PT Nusantara Ekspres Kilat. Terdapat indikasi bahwa jabatan rangkap yang dilakukan oleh Direktur PT Shopee International Indonesia dan PT Nusantara Ekspres Kilat melanggar Pasal 26 Undang-Undang Nomor 5 Tahun 1999. Jabatan rangkap yang dilakukan oleh Direktur PT Shopee International Indonesia dan PT Nusantara Ekspres Kilat menimbulkan implikasi yuridis yang signifikan terhadap kebijakan-kebijakan di platform Shopee. Shopee telah melakukan praktik diskriminasi dalam pemilihan layanan pengiriman di platformnya, yang hal ini melanggar Pasal 19 huruf d UU No. 5 Tahun 1999. KPPU melakukan sidang perdana terhadap dugaan pelanggaran Shopee terhadap UU No. 5 Tahun 1999 pada Mei 2024. Kata Kunci: jabatan rangkap, direktur, platform Shopee